Analisis Peran Kepemimpinan dalam Membangun Budaya Organisasi yang Produktif di Dinas Sosial Kota Gunungsitoli (Lembaga Pengembangan Kinerja Dosen, 2025)
Leadership plays a crucial role in shaping a productive organizational culture within the public bureaucracy. This study aims to analyze how leadership contributes to building a productive organizational culture at the Social Service Office of Gunungsitoli City, as well as to identify the challenges and strategies implemented in the process. The research uses a descriptive qualitative approach with data collection techniques including interviews, observation, and document studies. The data analysis technique follows the model of Miles, Huberman, and Saldana, which includes data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that transformational and participative leadership significantly contributes to creating a conducive work climate, encouraging employee engagement, and enhancing loyalty and work enthusiasm. These leadership traits are reflected in open communication, employee involvement in decision-making, and recognition of performance. The main challenges in implementing a productive organizational culture include limited human resources, rigid bureaucratic culture, and suboptimal use of data in decision-making. To address these challenges, leaders apply dialogical supervision strategies, utilize meetings as strategic coordination forums, and promote training and digitalization of reporting systems. The results of this study are expected to serve as a basis for developing more adaptive and performance-oriented leadership in the public sector.